2011
DOI: 10.1007/s11164-011-0248-4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of scandia-doped tungsten powders prepared by a spray-drying method

Abstract: Scandium oxide-doped tungsten powders were prepared by a new method of spray drying combined with two-step hydrogen reduction. The particle size of doped tungsten, powder morphology, and distribution of doped scandium oxide were characterized by scanning electron microscopy, X-ray diffraction, and laser diffraction particle size analysis. Experimental results indicated that the predecessor powders prepared by spray drying were spherical in shape. Two compounds, WO 3 and Sc 2 W 3 O 12 , in the raw powder calcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…The two hydrogen consumption peaks at 525°C and 700°C might be caused by the reduction of two stages for WO 3 → WO 2 and WO 2 → W, respectively. On the other hand, compared with the pure tungsten oxide powders [16], it is obvious that the TPR spectra of scandiadoped tungsten oxide powders have been shifted to a lower temperature, indicating that Sc 2 O 3 leads to a decrease of the reduction temperature of the doped powders. Based on the TPR result, it could be deduced that reduction at the temperature >700°C will get scandia-doped tungsten powders.…”
Section: A Characterization Of Scandia-doped Tungsten Powdersmentioning
confidence: 98%
See 1 more Smart Citation
“…The two hydrogen consumption peaks at 525°C and 700°C might be caused by the reduction of two stages for WO 3 → WO 2 and WO 2 → W, respectively. On the other hand, compared with the pure tungsten oxide powders [16], it is obvious that the TPR spectra of scandiadoped tungsten oxide powders have been shifted to a lower temperature, indicating that Sc 2 O 3 leads to a decrease of the reduction temperature of the doped powders. Based on the TPR result, it could be deduced that reduction at the temperature >700°C will get scandia-doped tungsten powders.…”
Section: A Characterization Of Scandia-doped Tungsten Powdersmentioning
confidence: 98%
“…It can be found that doping with scandium oxide has a remarkable influence on the reduction process of the powders. It has been reported that the reduction of pure WO 3 → W consists of three reduction stages, i.e., WO 3 → WO 2.9 , WO 2.9 → WO 2 , and WO 2 → W [16], however, the reduction process of scandiadoped tungsten powders was divided into two stages. The results reveal that the hydrogen consumption corresponding to the two-step reduction of WO 3 → WO 2.9 → WO 2 has merged into one peak.…”
Section: A Characterization Of Scandia-doped Tungsten Powdersmentioning
confidence: 99%
“…3) Sc-in-oxides: A related approach implemented by Cui et al [123]- [125] prepares Sc 2 O 3 -doped pressed cathodes by fabricating Sc 2 O 3 and Ba-Ca-aluminate co-doped W powders using a spray drying method and a two-step hydrogen reduction process. In this "Ba scandate" or "scandiadoped powder (SDP)" fabrication approach, cathode pellets are pressed and sintered from a mixture of W powder and various Ba x Sc y O x+ 3 2 y powders [11], [126].…”
Section: A Fabricationmentioning
confidence: 99%